Remarks on career perspectives for BA German graduates from Universiti Putra Malaysia (the 2009 & 2010 graduates) - Schaar, Torsten; Ogasa, Nicole; Ang, Lay Hoon (2015)
In January 2015, the 10th batch of BA German students graduated from Universiti Putra Malaysia (UPM) and joined the changing and challenging Malaysian labor market. Since its introduction, 164 Malaysian undergraduates have completed the BA German programme, a combination of language instruction, philological and market-oriented German courses. A survey into the professional development of BA German students since their graduation (the first batch graduated in 2004) revealed that the majority of graduates had no problems in finding employment in the corporate or education sector shortly after finishing their studies. Many have changed their career paths several times in order to gain higher incomes, face greater challenges and enjoy better career opportunities. Some graduates also became teachers of German or other languages (Bahasa Malaysia, English, and Mandarin) as well as for science subjects at primary and residential schools, colleges and universities. Furthermore, several opted for Master’s degrees and PhD’s. The tracer study project aimed to provide more comprehensive data on the professional development of BA German graduates from UPM, which allowed the conclusion that studying BA German at UPM combined with a business-related minor subject is a proven formula for a successful and quick entry into the Malaysian job market.